Critical factors for SMEs' B2B e-marketplaces: A literature review / Zazaleena Zakariah, Nursyahidah Alias and Norjansalika Janom - Zakariah, Zazaleena; Alias, Nursyahidah; Janom, Norjansalika (2010)
The integration of SMEs in Malaysia into existing B2B value chains are believed to be so far behind expectations. Technologies and approaches in the field of e-commerce are not mature enough in order to allow for their broad successful commercial applications especially to SMEs. Even though there is now an interesting and growing number of studies addressing B2B e-commerce adoption within the specific context of SMEs, little research has been conducted in developing countries, especially Malaysia. Thus, this study seeks to fill this gap to help understand the factors that hinder the adoption of lCT and e-commerce by SMEs in their trading transaction, and to explore how best they can be overcome. Furthermore, the finding can be used to identify the critical factors in ensuring B2B e-marketplaces success. Hence, help to further understand the slow adoption lagging of B2B e-marketplaces based on Malaysia phenomena.